Drama, Poetry and Music in Late-Renaissance Italy - Cox, Virginia; Sampson, Lisa (UCL Press, 2023)
Leonora Bernardi (1559-1616), a gentlewoman of Lucca, was a highly regarded poet, dramatist and singer. She was active in the brilliant courts of Ferrara and Florence at a time when creative women enjoyed exceptional visibility in Italy. Like many such figures, she has since suffered historical neglect. Drama, Poetry and Music in Late-Renaissance Italy presents the first ever study of Bernardi’s life, and modern edition of her recently discovered literary corpus, which mostly exists in manuscript. Her writings appear in the original Italian with new English translations, scholarly notes, critical essays and contributions by Eric Nicholson, Eugenio Refini and Davide Daolmi